Exported J domain proteins of the human malaria parasite - Almaazmi, Shaikha Y.; Singh, Harpreet; Dutta, Tanima; Blatch, Gregory L. (Frontiers in Molecular Biosciences, 2022)
The heat shock protein 40 (Hsp40) family, also called J domain proteins (JDPs), regulate their Hsp70 partners by ensuring that they are engaging the right substrate at the right time and in the right location within the cell. A number of JDPs can serve as co-chaperone for a particular Hsp70, and so one generally finds many more JDPs than Hsp70s in the cell. In humans there are 13 Hsp70s and 49 JDPs. The human malaria parasite, Plasmodium falciparum, has dedicated an unusually large proportion of its genome to molecular chaperones, with a disproportionately high number of JDPs (PfJDPs) of 49 members. Interestingly, just under half of the PfJDPs are exported into the host cell during the asexual stage of the life cycle, when the malaria parasite invades mature red blood cells. Recent evidence suggests that these PfJDPs may be functionalizing both host and parasite Hsp70s within the infected red blood cell, and thereby driving the renovation of the host cell towards pathological ends. PfJDPs have been found to localize to the host cytosol, mobile structures within the host cytosol (so called “J Dots”), the host plasma membrane, and specialized structures associated with malaria pathology such as the knobs. A number of these exported PfJDPs are essential, and there is growing experimental evidence that they are important for the survival and pathogenesis of the malaria parasite. This review critiques our understanding of the important role these exported PfJDPs play at the host-parasite interface.